The altered immunological status of children conceived by assisted reproductive technology - Xin Xu; Han Wu; Yuehong Bian; Linlin Cui; Yuanyuan Man; Zhao Wang; Xin Zhang; Changming Zhang; Ling Geng (BMC, 2021)
Abstract Background With the increased use of assisted reproductive technology (ART), assessing the potential health risks of children conceived on ART important to public health. Most research in this area has focused on the effects of ART on perinatal, metabolic, and oncological risks in children. Although an increased risk of immune-related diseases has been reported in children born after ART, there are no studies on the immunological status of these children. This study aimed to evaluate the impact of different embryo transfer methods and fertilization strategies on the immune status of the offspring. Methods A total of 69 children born to women treated with ART and a matched control group of 17 naturally conceived (NC) children, all aged from 3 to 6 years, were recruited in the reproductive hospital affiliated to Shandong University. The frequency of immune cells in the peripheral blood was assayed using flow cytometry; plasma cytokine levels were determined by multiplex cytokine immunoassay with human cytokine magnetic beads. Results Compared to children born after natural conception, children born after ART had elevated interferon-γ (IFN-γ) levels, regardless of embryo transfer and fertilization strategies. Children in the fresh-embryo transfer group had significantly higher IL-4 levels and a lower ratio of IFN-γ to IL-4 than those in the NC group ((P = 0.004, 10.41 ± 5.76 pg/mL vs 18.40 ± 7.01 pg/mL, P = 0.023, 1.00 ± 0.48 vs 0.67 ± 0.32, respectively). Similar results were shown in either the in vitro fertilization (IVF) group or the intra-cytoplasmic sperm injection (ICSI) group (P < 0.05 and P = 0.08 for IVF; P < 0.05 and P < 0.05 for ICSI, respectively). These alterations in IL-4 concentrations and the ratio of IFN-γ to IL-4 were statistically significantly correlated with supra-physical E2 (estradiol) levels on the day of hCG administration (R = 0.502, P = 0.017; R = − 0.537, P = 0.010, respectively). Consistently, the frozen embryo transfer did not result in alterations of these immune indicators in the offspring. Overall, there were no significant differences between the ART group and NC group in the frequencies of T cells, B cells, natural killer (NK) cells, CD4+T cells, CD8+T cells, T helper (TH)1 cells, TH17 cells, and regulatory T (Treg) cells and cytokine levels of IL-10 and IL-17a (all P > 0.05). Conclusions Immunological alterations existed in children born after the use of ART. The elevated E2 levels before embryo implantation contributed to the increased IL-4 levels in children conceived by fresh embryo transfer. The assessment of immunological alteration is of importance to children conceived by ART for early monitoring and intervention.